Implementing Differentiated Instruction in an EFL Classroom: A Study of Grade VIII Students at SMPIT MTA Karanganyar - Fitria Faida Amanina; Nur Hidayat (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
Differentiated Instruction (DI) is essential in Indonesian EFL classrooms to address diverse student needs under the Merdeka Curriculum. The purpose of this study is to describe the implementation of Differentiated Instruction (DI) in English as a Foreign Language (EFL) learning, identify the challenges faced by teachers during the implementation process, and formulate strategies used to overcome these obstacles. This study used qualitative methods with data collection techniques in the form of observation, interviews, and questionnaires. The research procedure included conducting non-cognitive diagnostic assessments, analyzing student needs, preparing differentiated lesson plans, conducting classroom learning, and collecting data on teacher and student perceptions through semi-structured interviews. The research subjects included two English teachers and seventh and eighth grade students selected based on variations in academic ability to illustrate the diversity of learning needs. The results showed that teachers had implemented Differentiated Instruction through content, process, and product differentiation, particularly by providing materials of varying levels of difficulty, grouping based on ability, and using a variety of learning media. The main challenges in implementing DI included time constraints, the complexity of classroom management, and administrative burdens. Teachers overcame these obstacles through flexible strategies, creativity in preparing materials, the use of technology, and the creation of a supportive learning environment. Students generally showed positive perceptions, feeling more helped because the tasks were tailored to their abilities and interests, and more motivated to be actively involved in learning.